(untitled) (Bangladesh Journal of Medical Microbiology, 2019)
There is a high prevalence of H. pylori infection in Bangladeshi population that causes site specific diseases which includes gastritis, gastric ulcer, duodenal ulcer and gastric carcinoma. The Cross sectional study was carried out in the Department of Microbiology and immunology, Bangabandhu Medical University (BSMMU), during the period of September, 2018 to July, 2019. Dyspeptic patients, who underwent endoscopic examination at the Department of Gastroenterology of Dhaka medical College and Hospital, who fulfilled the inclusion criteria were enrolled as study population. Collected gastric and duodenal biopsy specimens from 142 patients were categorized as H. pylori positive cases (34.5%) and H. pylori negative cases (35.2%) based on the case definition used in the study by RUT, Histology and ureC gene PCR. All of the laboratory works were performed at Department of Microbiology and Immunology except Histology which was performed at the Department of Pathology of BSMMU. Endoscopic findings significantly co-related with histological findings (p = 0.001). Highest rate of H. pylori infection was found in 76% of duodenal ulcer cases and lowest in Adenocarcinoma group being only 9% of total study population. H. pylori infection was positively associated with duodenal ulcer cases (p=0.014) and negatively with adeno carcinoma cases (p=0.002) in a statistically significant manner. Bangladesh J Med Microbiol 2019; 13 (2): 11-17